Terapi Self Healing dalam Menurunkan Kecemasan Selama Kehamilan di Era Pandemi Covid-19 - Nining Mustika Ningrum (Program Studi S1 Kebidanan - Fakultas Sains dan Kesehatan Universitas PGRI Adi Buana Surabaya, 2021)
Every pregnant woman experiences anxiety in pregnancy, the anxiety increases with the Covid-19 pandemic and the increase in cases of pregnant women's deaths caused by Covid-19. Excessive fear in pregnant women due to this pandemic causes mothers to experience anxiety and worry in pregnancy. Type of quantitative analytical research, research design used Quasi Eksperiment One group pre-post test design is to apply Self-Healing (Self compassion) applied every morning when waking up and at night before going to bed and done regularly for 3 months. A sample of 120 pregnant women with purposive sampling techniques. Intrumen: HARS (Hamilton Anciety Rating Scale), Ceklist and Observation sheet, data analyzed using the Wilcoxon Test. Most of the respondents before Self-Healing therapy, 62.5% had moderate anxiety levels and after doing Self-Healing therapy, the respondents were mild, which was 77.5%. Analysis with the Wilcoxon Test obtained a p-value of 0.001 correlation coefficient (r) 0.125 which can be concluded there is an effect of Self-Healing therapy on decreased anxiety during pregnancy.